2017
DOI: 10.1002/adfm.201606545
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Tri‐Cation and Dual‐Anion Mixed Perovskite Solar Cells by Au@SiO2 Nanoparticles

Abstract: Tri-cation and dual-anion mixed perovskites have been widely utilized in perovskite solar cell (PSC) applications due to their novel properties such as high absorption, high stability, and low cost. To commercialize the PSCs, further improving the device performance without detrimentally changing the device configuration is important at present. Herein, Au@SiO 2 nanoparticles (NPs) are introduced to modify the interface between mesoporous TiO 2 (mp-TiO 2 ) and mixed perovskite with increased main photovoltaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 51 publications
(78 reference statements)
3
80
0
Order By: Relevance
“…Furthermore, Wang and Snaith have incorporated Au NPs into mesoporous Al 2 O 3 layer, but they proposed that the SPR effect has little influence on light absorption, and ascribed their IPCE enhancement to the improvement of charge separation. Recently, Ye et al incorporated Au NPs into absorber/HTL interface, and they found a more significant enhancements in all photovoltaic parameters mainly due to the improved mobility of the charge carriers . All these findings suggest that the SPR of metallic nanoparticles in PSCs strongly rely on the doping concentration and location, and the incorporating of Au NPs in bulk films requires large concentration to keep interval distance, which will cause worse device performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Wang and Snaith have incorporated Au NPs into mesoporous Al 2 O 3 layer, but they proposed that the SPR effect has little influence on light absorption, and ascribed their IPCE enhancement to the improvement of charge separation. Recently, Ye et al incorporated Au NPs into absorber/HTL interface, and they found a more significant enhancements in all photovoltaic parameters mainly due to the improved mobility of the charge carriers . All these findings suggest that the SPR of metallic nanoparticles in PSCs strongly rely on the doping concentration and location, and the incorporating of Au NPs in bulk films requires large concentration to keep interval distance, which will cause worse device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the induced surface resonant of free electrons at a certain incident light, metallic nanoparticles exhibit a surface plasmon resonance (SPR) and could also act as scattering centers . In the past few years, scientists have tried to incorporate gold nanoparticles (Au NPs) into PSCs to improve the light absorption and PCE .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An effective method has also been investigated in perovskite devices to achieve efficient performance by combinational use of Au NPs insulating by MgO [8]. Also, different amount of Au@SiO2 core-shell NPs have been deposited as a modifier of the mp-TiO2 layer in perovskite solar cells, and the enhanced in device performance and increase in light absorption are reported [9].…”
Section: Introductionmentioning
confidence: 99%